Job creation and firm-specific location incentives. (29th March 2016) - Jensen, Nathan M.
Abstract: Government economic development programmes provide opportunities for firms to leverage financial incentives for business expansion and relocation. This article examines the ability of these incentives to promote employment. Using establishment-level data from the state of Kansas as well as original firm-level survey data, I evaluate the effectiveness of financial incentives in creating jobs through recipient firms. My findings from the establishment-level data indicate that incentive programmes have no discernable impact on firm expansion, measured by job creation. In addition, the survey data suggest that incentive recipients highly recommend this programme to other firms, but few firms actually increased their employment in Kansas because of these incentives; similarly, very few firms would have left the state if they had not benefited from this programme. Thus, incentives have little impact on the relocation or expansion decisions of firms.